Local Wisdom as A Foundation of Harmony and Tolerance Between Islamic Streams iIn Tambakboyo Hamlet Klakah Lumajang - Umam, M. Nur Khotibul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Tambakboyo Hamlet, located in Klakah Village, Lumajang Regency, is a hamlet inhabited by a Muslim community with diverse Islamic backgrounds, such as the Nahdlatul Ulama (NU) and Muhammadiyah organizations. Due to these differences, religious understanding and practices tend to potentially cause conflict. This research aims to explore how local wisdom plays a role in maintaining tolerance and strengthening Islamic values among Muslims with different understanding backgrounds. The object of this research is the Muslim community in Tambakboyo Hamlet which consists of several Islamic sects, as well as the social interactions between them. This research aims to identify and analyze how local wisdom in Tambakboyo Hamlet plays a role in maintaining harmony and tolerance between Islamic sects, as well as how Islamic values can be enriched and strengthened. This research uses a qualitative approach with a case study method. Data was collected through participant observation and in-depth interviews with religious leaders and the local community. The research results show that local traditions, such as cooperation, village meetings, and respect for leaders of religious organizations, play a central role in building open communication and mutual respect between groups, thus becoming an important foundation in maintaining social and spiritual stability. It can be concluded that strengthening Islamic values through local wisdom can create harmonious and sustainable harmony.